Review Analisis Efektivitas dan Risiko Toksisitas Aminofilin pada Pengobatan Penyakit Asma - Nurma Dwi Rahmawati; Indah Laily Hilmi; Salman Salman (Journal of Pharmaceutical and Sciences, 2023)
Asthma is a chronic inflammatory disease of the airways that involves many cells and factors. Physiologically, asthma is characterized by narrowing of the airways that causes increased hypersensitivity which is characterized by repeated episodic symptoms of wheezing, shortness of breath, chest tightness, and coughing, especially at night and or in the morning. The World Health Organization (WHO) estimates that the number of asthmatic diseases in 2019 is around 235 million. Asthma is a worldwide health problem, affecting approximately 1-18% of the population in various countries around the world. Aminophylline is the most common asthma drug used to treat asthma in Indonesia and is a drug with a narrow therapeutic range with a high risk of adverse drug reaction (ADR). Improper use of aminophylline will cause many side effects that can potentially be fatal and can actually make a person experience medical problems due to side effects that are more severe than the main medical problem. The purpose of this review article is to analyze the effectiveness and risk of aminophylline in the treatment of asthma using a literature study method taken from various international and national journals. Based on the results of the literature study, it was found that aminophylline in its use produces a toxic effect that is greater than its effectiveness.